, , ,

<<


 >>  ()
Pages:     | 1 | 2 ||

Ȼ ...

-- [ 3 ] --

C A=bK/(bN2F+bN3F) C B=K A L1=L1F*(0.079+A*(bN2+bN3)+B) C bL2F=0. C bL3F=0. C bN0= C bREF=497. c bT1=0.98;

C bT2=3. C bT3=7. C bN1C= C bN2C= C bN3C= C bN1F=bN0*(1-EXP(-L1F*bT1))/L1F C bN2F=bN0*EXP(-L1F*bT1)*(1-EXP(-bL2F*(bT2-bT1)))/bL2F C bN3F=bN0*EXP(-L1F*bT1-bL2F*(bT2-bT1))*(1-EXP(-bL3F*(bT3 bT2)))/bL3F A bL2=bL2F A bL3=bL3F A bTAU1=(EXP(L1*bT1)-1)/L A bTAU2=(EXP(bL2*(bT2-bT1))-1)/bL A bTAU3=(EXP(bL3*(bT3-bT2))-1)/bL A bTAU1_=L1/(EXP(L1*bT1)-1) A bTAU2_=bL2/(EXP(bL2*(bT2-bT1))-1) A bTAU3_=bL3/(EXP(bL3*(bT3-bT2))-1) A bqR=(0.94+0.06*bN3/bN3F) A bRE=bREF*bqR A bRE_bN3=bRE*bN L bN1=(-1/bTAU1-L1)*bN1+bRE*bN L bN2=1/btau1*bN1-((bL2+ 1/btau2)*bN2)) L bN3=1/btau2*bN2-((bL3+ 1/btau3)*bN3)) A BN=BN1+BN2+BN N bN1=bN1F+bN1C N bN2=bN2F+bN2C N bN3=bN3F+bN3C out TIME,bTAU1_,bTAU2_,bTAU3_ out TIME,bn1,bn2,bn 1.2. DYNAMO

C DT=0. C FINISH= C PERIOD=0. C START= L TIME= N TIME=START C L1F=5.69 ;

Lambda ..

C K=0.698 ;

% ..

C bK=0.223 ;

% ..

C A=bK C B=K/(N2F+N3F) A L1=L1F*(0.079+A+B*(N2+N3)) C L2F=0. C L3F=0. C N0= C N1C= C N2C= C N3C= C REF=597. T1= C T2=2. C T3=6. A L2=L2F A L3=L3F C N1F=N0*(1-EXP(-L1F*T1))/L1F C N2F=N0*EXP(-L1F*T1)*(1-EXP(-L2F*(T2-T1)))/L2F C N3F=N0*EXP(-L1F*T1-L2F*(T2-T1))*(1-EXP(-L3F*(T3-T2)))/L3F A TAU1=1/0.0192;

(EXP(L1*T1)-1)/L C TAU2=1/0.3834;

(EXP(L2F*(T2-T1))-1)/L2F C TAU3=1/0.0479;

(EXP(L3F*(T3-T2))-1)/L3F A TAU1_=L1/(EXP(L1*T1)-1) C TAU2_=L2F/(EXP(L2F*(T2-T1))-1) C TAU3_=L3F/(EXP(L3F*(T3-T2))-1) A qR=(0.617*N1/N1F+0.383) A RE=REF*qR L N1=(-L1-(1/TAU1))*N1+RE*N L N2=1/TAU1*N1-(L2+(1/TAU2))*N L N3=1/TAU2*N2-(L3+(1/TAU3))*N A N=N1+N2+N N N1=N1F+N1C N N2=N2F+N2C N N3=N3F+N3C out TIME,n1,n2,n 1.3. DYNAMO

C DT=0. C FINISH= C PERIOD=0. C START= L TIME= N TIME=START C L1F=5. C mN0= C mRef=244. C mRE=mREF C mT1=0. C mT2=1. C mN1C= C mN2C= C mN1F=mN0*(1-EXP(-L1F*mT1))/L1F C mN2F=mN0*EXP(-L1F*mT1)*(1-EXP(-L1F*(mT2-mT1)))/L1F A mTAU1=(EXP(L1*mT1)-1)/L A mTAU2=(EXP((L1*(mT2-mT1)))-1)/L A mTAU1_=L1/(EXP(L1*mT1)-1) A mTAU2_=L1/(EXP((L1*(mT2-mT1)))-1) L mN1=(-1/mTAU1-L1)*mN1+mRE*mN L mN2=1/mTAU1*mN1-(L1+1/mTAU2)*mN A mN=mN1+mN N mN1= mN1F+mN1C N mN2= mN2F+mN2C out TIME,mn1,mn 1.4. DYNAMO

C DT=0. C FINISH= C PERIOD=0. C START= L TIME= N TIME=START C L1F=5.69 ;

Lambda ..

C K=0.698 ;

% ..

C bK=0.223 ;

% ..

C A=bK C B=K/(N2F+N3F) A L1=L1F*(0.079+A+B*(N2+N3)) ;

======================================================== ;

C L2F=0. C L3F=0. C N0= C N1C= C N2C= C N3C= C REF=597. T1= C T2=2. C T3=6. A L2=L2F A L3=L3F C N1F=N0*(1-EXP(-L1F*T1))/L1F C N2F=N0*EXP(-L1F*T1)*(1-EXP(-L2F*(T2-T1)))/L2F C N3F=N0*EXP(-L1F*T1-L2F*(T2-T1))*(1-EXP(-L3F*(T3-T2)))/L3F A TAU1=(EXP(L1*T1)-1)/L C TAU2=(EXP(L2F*(T2-T1))-1)/L2F C TAU3=(EXP(L3F*(T3-T2))-1)/L3F A TAU1_=L1/(EXP(L1*T1)-1) C TAU2_=L2F/(EXP(L2F*(T2-T1))-1) C TAU3_=L3F/(EXP(L3F*(T3-T2))-1) A qR=(0.07*(N1)/(N1F)+0.93*(mN1+mN2)/(mN1F+mN2F)) A RE=REF*qR L N1=(-L1-(1/TAU1))*N1+RE*N L N2=1/TAU1*N1-(L2+(1/TAU2))*N L N3=1/TAU2*N2-(L3+(1/TAU3))*N A N=N1+N2+N N N1=N1F+N1C N N2=N2F+N2C N N3=N3F+N3C ;

======================================================= ;

C mN0= C mRef=244. C mRE=mREF C mT1=0. C mT2=1. C mN1C= C mN2C= C mN1F=mN0*(1-EXP(-L1F*mT1))/L1F C mN2F=mN0*EXP(-L1F*mT1)*(1-EXP(-L1F*(mT2-mT1)))/L1F A mTAU1=(EXP(L1*mT1)-1)/L A mTAU2=(EXP((L1*(mT2-mT1)))-1)/L A mTAU1_=L1/(EXP(L1*mT1)-1) A mTAU2_=L1/(EXP((L1*(mT2-mT1)))-1) L mN1=(-1/mTAU1-L1)*mN1+mRE*mN L mN2=1/mTAU1*mN1-(L1+1/mTAU2)*mN A mN=mN1+mN N mN1= mN1F+mN1C N mN2= mN2F+mN2C out TIME,n1,n2,n3,mn1,mn 1.5. , DYNAMO

;

3 ;

( ) ;

L1F=5. ;

| | ;

REF=597.33 | bREF=497.88 | mREF=244.9327;

211. ;

T1=1 | bT1=0.98 | mT1=0. ;

T2=2.5 | bT2=3.5 | mT2=1. ;

T3=6.5 | bT3=7.5 | mTAU1_=0. ;

L2F=0.68 | bL2F=0.48 | mTAU2_=0. ;

TAU1_=0.0192 | bTAU1_=0.0216 | mN0= ;

TAU2_=0.3834 | bTAU2_=0.204 | mN1F=401. ;

TAU3_=0.0479 | bTAU3_=0.082 | mN2F=9. ;

N0=213 | bN0=59 | ;

N1F=37.3075 | bN1F=10.3298 | ;

N2F=0.6768 | bN2F=0.3266 | ;

N3F=0.3565 | bN3F=0.1185 | ;

|||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||| C DT=0. C FINISH= C PERIOD=0. C START= L TIME= N TIME=START C L1F=5.69;

Lambda ..

C K=0.698 ;

% ..

C bK=0.223 ;

% ..

C A=bK/(bN2F+bN3F) C B=K/(N2F+N3F) A L1=L1F*(0.079+A*(bN2+bN3)+B*(N2+N3)) ;

======================================================== ;

C L2F=0. C L3F=0. C N0= C N1C= C N2C= C N3C= C REF=597.33;

T1= C T2=2. C T3=6. A L2=L2F A L3=L3F C N1F=N0*(1-EXP(-L1F*T1))/L1F C N2F=N0*EXP(-L1F*T1)*(1-EXP(-L2F*(T2-T1)))/L2F C N3F=N0*EXP(-L1F*T1-L2F*(T2-T1))*(1-EXP(-L3F*(T3-T2)))/L3F A TAU1=(EXP(L1*T1)-1)/L C TAU2=(EXP(L2F*(T2-T1))-1)/L2F C TAU3=(EXP(L3F*(T3-T2))-1)/L3F A TAU1_=L1/(EXP(L1*T1)-1) C TAU2_=L2F/(EXP(L2F*(T2-T1))-1) C TAU3_=L3F/(EXP(L3F*(T3-T2))-1) A qR=(0.07*(N1+bN1)/(N1F+bN1F)+0.93*(mN1+mN2)/(mN1F+mN2F)) A RE=REF*qR L N1=(-L1-(1/TAU1))*N1+RE*N L N2=1/TAU1*N1-(L2+(1/TAU2))*N L N3=1/TAU2*N2-(L3+(1/TAU3))*N A N=N1+N2+N N N1=N1F+N1C N N2=N2F+N2C N N3=N3F+N3C ;

======================================================== ;

C bL2F=0. C bL3F=0. C bN0= C bREF=497. bT1=0. C bT2=3. C bT3=7. C bN1C= C bN2C= C bN3C= C bN1F=bN0*(1-EXP(-L1F*bT1))/L1F C bN2F=bN0*EXP(-L1F*bT1)*(1-EXP(-bL2F*(bT2-bT1)))/bL2F C bN3F=bN0*EXP(-L1F*bT1-bL2F*(bT2-bT1))*(1-EXP(-bL3F*(bT3 bT2)))/bL3F A bL2=bL2F A bL3=bL3F A bTAU1=(EXP(L1*bT1)-1)/L A bTAU2=(EXP(bL2*(bT2-bT1))-1)/bL A bTAU3=(EXP(bL3F*(bT3-bT2))-1)/bL3F A bTAU1_=L1/(EXP(L1*bT1)-1) A bTAU2_=bL2/(EXP(bL2*(bT2-bT1))-1) A bTAU3_=bL3F/(EXP(bL3F*(bT3-bT2))-1) A bqR=(0.37*(N1+bN1)/(N1F+bN1F)+0.63*(mN1+mN2)/(mN1F+mN2F)) A bRE=bREF*bqR A bRE_bN3=bRE*bN L bN1=(-1/bTAU1-L1)*bN1+bRE*bN L bN2=1/btau1*bN1-((bL2+ 1/btau2)*bN2)) L bN3=1/btau2*bN2-((bL3+ 1/btau3)*bN3)) A BN=BN1+BN2+BN N bN1=bN1F+bN1C N bN2=bN2F+bN2C N bN3=bN3F+bN3C ;

======================================================== ;

C mN0= C mRef=244.932684;

314;

342.375;

C mRE=mREF C mT1=0. C mT2=1. C mN1C= C mN2C= C mN1F=mN0*(1-EXP(-L1F*mT1))/L1F C mN2F=mN0*EXP(-L1F*mT1)*(1-EXP(-L1F*(mT2-mT1)))/L1F A mTAU1=(EXP(L1*mT1)-1)/L A mTAU2=(EXP((L1*(mT2-mT1)))-1)/L A mTAU1_=L1/(EXP(L1*mT1)-1) A mTAU2_=L1/(EXP((L1*(mT2-mT1)))-1) L mN1=(-1/mTAU1-L1)*mN1+mRE*mN L mN2=1/mTAU1*mN1-(L1+1/mTAU2)*mN A mN=mN1+mN N mN1= mN1F+mN1C N mN2= mN2F+mN2C ;

======================================================== out TIME,n1,n2,n3,bn1,bn2,bn3,mn1,mn

Pages:     | 1 | 2 ||
 
 >>  ()





 
<<     |    
2013 www.libed.ru - -

, .
, , , , 1-2 .